2018
DOI: 10.1016/j.mayocp.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

HFpEF, a Disease of the Vasculature: A Closer Look at the Other Half

Abstract: Patients with heart failure are commonly divided into those with reduced ejection fraction (EF<40%) and those with preserved ejection fraction (HFpEF; EF>50%). For heart failure with reduced EF, a number of therapies have been found to improve patient morbidity and mortality, and treatment is guideline based. However for patients with HFpEF, no treatment has been found to have clinical benefit. To objectively assess treatments for HFpEF, a comprehensive PubMed literature search was performed using the terms HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 58 publications
(105 reference statements)
2
37
1
1
Order By: Relevance
“…Diastolic intracellular calcium handling is a major determinant of LV relaxation. Dephosphorylated phospholamban (PLN) is an inhibitor of sarcoplasmic/endoplasmic reticulum Ca(2+)ATPase 2a (SERCA2a), but PKA-catalyzed (or CaMKII) phosphorylation of PLN results in the dissociation of PLN from SERCA2a, thus activating this Ca 2+ pump and augmenting SERCA2a activity (9,10). Cardiomyocyte Ca 2+ accumulation in the absence of concomitant enhancement of SERCA activity leads to elevated diastolic Ca 2+ , Ca 2+ transients with preserved or enhanced amplitude, and slower Ca 2+ reuptake kinetics with impaired relaxation.…”
Section: Diastolic Limitationsmentioning
confidence: 99%
“…Diastolic intracellular calcium handling is a major determinant of LV relaxation. Dephosphorylated phospholamban (PLN) is an inhibitor of sarcoplasmic/endoplasmic reticulum Ca(2+)ATPase 2a (SERCA2a), but PKA-catalyzed (or CaMKII) phosphorylation of PLN results in the dissociation of PLN from SERCA2a, thus activating this Ca 2+ pump and augmenting SERCA2a activity (9,10). Cardiomyocyte Ca 2+ accumulation in the absence of concomitant enhancement of SERCA activity leads to elevated diastolic Ca 2+ , Ca 2+ transients with preserved or enhanced amplitude, and slower Ca 2+ reuptake kinetics with impaired relaxation.…”
Section: Diastolic Limitationsmentioning
confidence: 99%
“…Chronic maladaptive neurohumoral activation leading to sustained systemic arterial hypertension has been implicated in the course of HFpEF [ 54 ]. Studies have shown that systemic hypertension is a critical determinant of outcome in HFpEF as it plays a crucial role in the onset and maintenance of a proinflammatory state, arterial stiffness, ventricular hypertrophy, titin-dependent stiffness, and dysfunction [ 55 57 ]. In patients with HFpEF, control of hypertension can induce regression of myocardial mass and improve cardiac function and relaxation as well as clinical outcomes [ 58 , 59 ].…”
Section: Hfpef and Hypertensionmentioning
confidence: 99%
“…The underlying causes of HFpEF, including hypertension, type 2 diabetes, and coronary artery disease, first damage the most susceptible longitudinally arranged subendocardial myocardial fibers, which lead to impairment of longitudinal function . A previous study also demonstrated that longitudinal function plays a key role in LV myocardial performance and global function in patients with HF .…”
Section: Discussionmentioning
confidence: 98%